Evaluation of Titanium Elastic Stable Intramedullary Nailing for Long Bone Fractures in Dogs - Kumar, Ankush; Chaudhary , Ram Nazar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted on ten clinical cases, diagnosed with long bone diaphyseal fractures selected randomly irrespective of their age, sex and breed. All the fractures were repaired with titanium elastic stable intramedullary nailing. Post-operative clinical and radiographic evaluations of the repaired bone were done immediately after the recovery from anaesthesia, and at 15th, 30th and 60th post-operative days. The results showed significant improvement in the weight bearing and functional limb usage score. Slight migration of the nail at the insertion site was observed in four cases which were easily managed without any serious complication. On radiographic evaluation a significant increase in bone formation score and bone union scores were observed post-operatively. Overall, the outcomes were favourable in dogs with respect to weight bearing, functional limb usage, bone formation, bone union and callus index with titanium elastic stable intramedullary nailing.